The Construction and Standardization of a Domestic Violence Questionnaire - Abolmaali, Khadijeh; Saberi, Hayedeh; Saber, Sousan (Scientific Research, 2014)
The purpose of this research was to standardize the self-reported domestic violence scale. 530 participants were randomly selected via clustered sampling methods from married students of The Islamic Azad University of district 8 in Iran. According to this scale, a total score was measured for domestic violence and also, based on exploratory factor analysis, 2 scores were measured for two dimensions of domestic violence, and these dimensions are: 1) Psycho-physical violence, 2) Control violence (sexual, economic, coercive violence). The reliability of this test was measured with internal consistency (α = 0.915) and the test retest method (r = 0.987). The criterion validity of this scale was significant and this scale had a significant relationship with the quality of marital life test. This scale can be used by psychologists and researchers for diagnostic assessment, intervening programs and identification of domestic violence dimensions.
Keywords: Domestic Violence Scale; Psycho-Physical Violence; Control Violence; Standardization; Reliability; Validity